Reconstruction and development in Nigeria : proceedings of a national conference - Ayida, Allison A.; Onitiri, H. M. A. (Ibadan : Published for the Nigerian Institute of Social and Economic Research by Oxford University Press, 1971)
This volume contains the papers read by Nigerian and foreign scholars at the Conference on National Reconstruction and Development in Nigeria held in March 1969, shortly before the end of the civil war. 9 text figures15 charts. The papers cover sub-themes like: development objectives; the development process; federalism economic planning and plan administration; agriculture and rural development; planning for further development; Nigeria$1 (Bs trade balance of payment and capital movement; main trends in banking and monetary policy in 1968; fiscal measures; prices, wages and costs; transport and communication systems; energy resources and utilisation; rehabilitation and settlement; education and manpower; health housing and social welfare.s
Includes bibliographical references.
lje 03/10/2018
Loans
Keywords: Economic developement; Economic growth; Nigeria